2019
DOI: 10.1016/j.toxrep.2019.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Clinico-epidemiology and management of Russell’s viper (Daboia russelii) envenoming in dogs in Sri Lanka

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 21 publications
(34 reference statements)
0
20
0
Order By: Relevance
“…Fang marks among the majority of dog victims of N. naja and Dabia russelii 21 , 22 are seen in the head and neck region and a similar bite distribution pattern was seen in the majority of HNPV bitten dogs. Sharp canine teeth have evolved as the major weapons for protection in dogs and they fight facing ahead.…”
Section: Discussionmentioning
confidence: 68%
See 4 more Smart Citations
“…Fang marks among the majority of dog victims of N. naja and Dabia russelii 21 , 22 are seen in the head and neck region and a similar bite distribution pattern was seen in the majority of HNPV bitten dogs. Sharp canine teeth have evolved as the major weapons for protection in dogs and they fight facing ahead.…”
Section: Discussionmentioning
confidence: 68%
“…Consistent with studies of snakebite incidence from other venomous snakes this study observed a higher proportion of males suffered HNPV bites. It is hypothesised this reflects the more prominent territorial behaviour of male dogs 8 , 22 , 23 . This observation parallels the incidence of snakebite in human males in farming communities due to social norms governing occupational roles 4 , 25 .…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations